Norms and Applications of the Combination of Contracts and Promises (Wa’ad) in Musyarakah Mutanaqisah Contracts - Azmi Nur Naila Najah; Muhammad Fauzan Januri (Mabahits Al-Uqud, 2024)
This paper examines the norms and application of the combination of contracts (uqd) and promises (wa’ad) in Musyarakah Mutanaqisah contracts. The study uses a qualitative method, with a deductive-normative approach to assess the legal standing of these concepts within Musyarakah Mutanaqisah. The research focuses on current conditions and uses secondary data such as books and legal regulations. Uqd refers to contracts involving mutual agreement through ijab and qabul, whereas wa’ad is a promise from one party to perform an act in the future. In Musyarakah Mutanaqisah agreements, these two concepts are applied together to facilitate the gradual transfer of asset ownership. The study finds that while wa’ad is not legally binding, it plays a significant role in ensuring adherence to Shariah principles while meeting business needs. The paper highlights the importance of understanding these concepts in the context of Islamic financial contracts.